Electrochemical water oxidation catalyzed by an in situ generated alpha-Co(OH)(2) film on zeolite-Y surface - Bose, Suranjana; Debgupta, Joyashish; Ramsundar, Rani M.; Das, Samar K. (Chemistry-A European Journal, 2017)
The design and synthesis of an efficient and robust water-oxidation catalyst with inexpensive materials remains an important challenge in the context of artificial photosynthesis. Herein, a simple but unique technique is reported to in situ generate a thin-film of alpha-Co(OH)(2) on the surface of zeolite-Y [hereafter referred to as Y-alpha-Co(OH)(2)] that acts as an efficient and stable catalyst for electrochemical water oxidation in alkaline medium. Catalyst Y-alpha-Co(OH)(2) is so stable that it retains its catalytic activity even after 2000 cyclic voltammetric cycles of water oxidation. Expectedly, the chemical composition of alpha-Co(OH)(2) on the surface of zeolite-Y remains same as that of parent Y-alpha-Co(OH)(2) after 2000 electrocatalytic cycles. A Tafel slope as low as 59 mV decade(-1) in 0.1m KOH (pH 13) suggests faster oxygen evolution kinetics (overpotential = 329 mV; turnover frequency = 0.35 mol O-2 (mol Co)(-1)s(-1) at 1 mA cm(-2)) than the existing alpha-Co(OH)(2)-based electrocatalysts operating in alkaline medium.